Changing LIBER - Fox, Peter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
LIBER, the Ligue des Bibliothèques Européennes de Recherche, has as its mission the representation and promotion of the interests of research libraries in Europe, the improvement of access to collections in European research libraries, and the provision of more efficient information services in Europe.